Evaluation of transcutaneous electrical acupoint stimulation for improving pain and cognitive function in elderly patients around the perioperative period of hip replacement surgery: A meta-analysis. - Sujuan Xu; Kai Huang; Qing Jiang (PLoS ONE)
Purpose We aim to evaluate the efficacy and safety of transcutaneous electrical acupoint stimulation(TEAS) in elderly patients around the perioperative period of hip replacement surgery. Methods The China National Knowledge Infrastructure(CNKI), Wangfang Data, VIP database, SinoMed, PubMed, and Embase databases were searched for relevant publications until August 2024. All randomized controlled studies evaluating the efficacy and safety of TEAS in patients around the perioperative period of hip replacement surgery. We calculated pooled risk ratio (RR) with 95% CIs for binary outcomes and standardized mean difference (SMD) for continuous outcomes. The Cochrane's Risk of Bias Tool were used to evaluate the quality of studies. Results A total of 13 studies with 946 patients were included in this analysis. 1-day visual analogue scale (VAS) scores and 2-day VAS scores were significantly lower in the TEAS group compared to the control group (SMD: -0.78, 95% CI: -1.47, -0.09, P = 0.02 and SMD:-0.54, 95% CI:-1.00,-0.09,P = 0.02). Furthermore, 1-day mini-mental state examination (MMSE) scores and 3-day MMSE scores were significantly higher in the TEAS group compared to the control group (SMD: 1.60, 95% CI: 0.68, 2.51,P<0.001 and SMD:1.31, 95% CI:1.03,1.59,P<0.001), along with a lower postoperative cognitive dysfunction rate (RR: 0.55, 95% CI: 0.41, 0.73, P<0.001). Conclusions Our meta-analysis demonstrated that TEAS significantly reduces pain and improves cognitive function in patients undergoing hip replacement surgery. Future studies should further investigate the optimal TEAS protocols to maximize these benefits across different population and surgical settings.